+0  
 
0
81
1
avatar

1. Simplify 2-1/4 over 3-1/5, provide your answer in the lowest terms.

2. Complete the following equation (4/2)[6-(-5)3]

Guest Sep 27, 2017
Sort: 

1+0 Answers

 #1
avatar+79786 
+1

2 - 1/4  =   (8/4)  - (1/4)   = 7/4

 

3 - 1/5  =    (15/5)  - (1/5)   = 14/5

 

So  

 

[ 2 - 1/4 ]                           7 / 4

_______       =               _____

[ 3 - 1/5 ]                         14 / 5

 

 

Keep the fraction in the numerator.......invert the fraction in the denominator and multiply the two......so we have

 

(7 / 4 )   (   5 / 14)   =      swap denominators

 

( 7 / 14)  ( 5 / 4)   =

 

(1 /2)  ( 5 / 4)  = 

 

5  / 8

 

 

 

(4/2)[6-(-5)3]    =

 

(2) [ 6 -  (-15) ]  =

 

(2)  [ 6 + 15 ] =

 

(2) [21 ]  =

 

42

 

 

cool cool cool

CPhill  Sep 27, 2017
edited by CPhill  Sep 27, 2017

17 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details